Energy Drink Consumption Among Finnish Adolescents: Prevalence, Associated Background Factors, Individual Resources, and Family Factors - Puupponen, Maija; Tynjälä, Jorma; Tolvanen, Asko; Välimaa, Raili; Paakkari, Leena (International Journal of Public Health, 2021)
Objectives Energy drink consumption has become a notable global phenomenon, with adolescents forming the main group of persons consuming these beverages. This is a matter of concern, since consumption has been associated with numerous negative health outcomes. In order to understand the popularity of energy drinks among adolescents, and to plan and target interventions, it is important to understand the determinants underpinning consumption. These, and the prevalence of consumption, have been underreported in Finland. Methods The data were drawn from the nationally representative Finnish Health Behaviour in School-aged Children (HBSC) surveys, conducted in 2014 and 2018, covering 7405 Finnish adolescents. Results Weekly energy drink consumption increased among Finnish adolescents between 2014 and 2018. In 2018, 25% of the adolescents surveyed reported weekly consumption of energy drinks. Boys typically consumed more than girls, and 15-year-olds more than 13-year-olds. Gender (boys more than girls), parental monitoring (more in the lower consumption group), school achievement (higher in the lower consumption group), and health literacy (higher in the lower consumption group) explained around 28% of the variance in weekly energy drink consumption in both years. However, when analysed all the background factors simultaneously, age (with higher consumption at 15 than 13) explained the variance only in 2018. Gender, parental monitoring, school achievement, and health literacy were equally strongly associated with weekly energy drink consumption in both years. Conclusions Energy drink consumption increased in Finland from 2014 to 2018, with weekly consumption varying according to background factors (gender, age), individual resources (educational aspiration, school achievement, health literacy), and family factors (parental monitoring).